Network policy making within the Turkish health sector : becoming collaborative - Hoxha, Julinda (Emerald Publishing Limited, 2020)
The study of policy networks is usually undertaken in the context of advanced democracies. Turkey, a case with the least favourable conditions for collaborative governance due to its tradition statist policy making and authoritarian political culture, is an under researched area in terms of exploring the network type of policy collaboration as a phenomenon. This book presents findings produced by micro- and meso-level analysis of policy networks using the Turkish context as a new case study. While this study does not suggest that centralized and hierarchical decision-making structures within the government are being replaced with horizontal and networked forms of governance, it demonstrates that networks have become an integral part of the practice of policy making within the Turkish health sector. These findings compel scholars of Turkish politics to expand the policy realm with new issues, actors, instruments, and concepts, and incorporates Turkey into general governance debates. Going beyond the confines of Turkish politics, these findings contradict the recent arguments that call into question the utility of policy networks as analytical concepts that can be used to explain policy making processes. Policy networks observed in the Turkish case consolidate research regarding treating networks seriously in public administration and public policy research. This book will prove invaluable for researchers and leaders in the fields of public administration and public policy, particularly within the Turkish context.
Includes index.
Keywords: Policy networks.; Medical policy -- Turkey.; Social Science -- Sociology -- General.; Social theory.; elektronické knihy; electronic books